2018
DOI: 10.1177/0033354918763168
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Algorithms to Improve the Accuracy of Unverified Diagnosis Codes for Birth Defects

Abstract: We found that surveillance programs that rely on unverified diagnosis codes can use algorithms to dramatically increase the accuracy of case finding, without having to review medical records. This can be important for etiologic studies. However, the use of increasingly restrictive case definition algorithms led to a decrease in completeness and the disproportionate exclusion of less severe cases, which could limit the widespread use of these approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 19 publications
3
17
0
Order By: Relevance
“…This finding, that algorithms designed to vary the number of diagnoses, medical encounters, and data sources can lead to an increase in PPV at the expense of case ascertainment has been reported previously. 15 Similarly, our findings that birth certificate flags have relatively high PPVs but miss a substantial number of confirmed cases is similar to other studies that report high PPVs for birth certificates but sensitivities ranging from 13% to 69%. 1,2,4,5 Our PPV results are consistent with several studies which reported PPVs of 37% to 63% but differ from those of Salemi et al, based on the Florida birth defects registry.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding, that algorithms designed to vary the number of diagnoses, medical encounters, and data sources can lead to an increase in PPV at the expense of case ascertainment has been reported previously. 15 Similarly, our findings that birth certificate flags have relatively high PPVs but miss a substantial number of confirmed cases is similar to other studies that report high PPVs for birth certificates but sensitivities ranging from 13% to 69%. 1,2,4,5 Our PPV results are consistent with several studies which reported PPVs of 37% to 63% but differ from those of Salemi et al, based on the Florida birth defects registry.…”
Section: Discussionsupporting
confidence: 91%
“…Restricting to inpatient codes improved PPVs but not substantially, and while the combination of a diagnosis code plus a procedure code resulted in high PPVs, this approach missed more than half of confirmed NTDs. This finding, that algorithms designed to vary the number of diagnoses, medical encounters, and data sources can lead to an increase in PPV at the expense of case ascertainment has been reported previously 15 . Similarly, our findings that birth certificate flags have relatively high PPVs but miss a substantial number of confirmed cases is similar to other studies that report high PPVs for birth certificates but sensitivities ranging from 13% to 69% 1,2,4,5 …”
Section: Discussionsupporting
confidence: 90%
“…Diagnoses made by the TBDR registry result from protocols that include active case‐finding, detailed medical record review and abstraction by surveillance specialists, and case classification by clinical geneticists. In contrast, diagnoses in the NIS rely exclusively on ICD‐based diagnoses without the possibility of any subsequent verification, resulting in suboptimal completeness and accuracy with considerable variation across specific defects (Salemi et al, ; Salemi, Rutkowski, Tanner, Matas, & Kirby, ). Missed diagnoses and false positive diagnoses are more likely with less severe birth defects; therefore, compared to the TBDR, the NIS may include a slight under‐representation of defects that would ultimately be classified as “not severe” in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that the algorithms used for BCCASS might not be applicable in other jurisdictions as they are dependent on local databases and jurisdiction-specific ICD coding practices. As previously suggested (Metcalfe et al, 2014;J. Salemi et al, 2018), programs should validate algorithms locally before implementing them for surveillance.…”
Section: Selected Congenital Heart Defectsmentioning
confidence: 99%
“…Algorithm accuracy is determined in comparison to a data source that is considered to be the reference standard (Chubak, Pocobelli, & Weiss, 2012). Several studies have reported on measures of accuracy for specific CA case definition algorithms (Eltonsy et al, 2017;J. Salemi et al, 2018;Metcalfe, Sibbald, Lowry, Tough, & Bernier, 2014).…”
Section: Introductionmentioning
confidence: 99%